2019
DOI: 10.29333/iji.2019.12233a
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relationship between Kolb’s Learning Styles, Gender and Learning American Slang‎ by Iranian EFL Students

Abstract: This study aimed to investigate the relationship between Kolb's learning styles and learning slang among Iranian EFL students with a gender-based focus. To this end, 63 EFL students of Tehran University were selected as the participants of the study out of 70 through the proficiency test by simple random sampling. The participants were both genders-27 males and 36 females aged between 18 and 25 in 2017-2018. Using descriptive statistics, correlation, regression and t-test, the data were analyzed. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
6
1
2
Order By: Relevance
“…Holtbrügge and Mohr [31] argue that male students prefer active experimentation to reflective observation more than female students. These findings contradict a number of previous studies which have found no impact of gender on students' learning style preferences [32][33][34][35][36][37][38]. In this regard, we suggest presenting a varied distance learning content adapted to meet the both male and female needs.…”
Section: Gender Effectcontrasting
confidence: 99%
“…Holtbrügge and Mohr [31] argue that male students prefer active experimentation to reflective observation more than female students. These findings contradict a number of previous studies which have found no impact of gender on students' learning style preferences [32][33][34][35][36][37][38]. In this regard, we suggest presenting a varied distance learning content adapted to meet the both male and female needs.…”
Section: Gender Effectcontrasting
confidence: 99%
“…This study adapts the Learning Style Inventory (LSI), which is based on Kolb's theory of experiential learning regarding the various approaches learners choose for perceiving and processing information. The LSI is frequently used as a predictive tool (for example, [22]- [24]). Some researchers have suggested that learning styles are related to culture [25], [26], are discipline specific [27], [28] and differ with respect to various other attributes [29].…”
Section: A Kolb's Learning Style Inventorymentioning
confidence: 99%
“…Según el objetivo pretendido se han elegido herramientas de diagnóstico y estrategias de aplicación. Gokalp, M. (2013), Gappi, L. L. (2013), Altun, H. (2019), Alnujaidi, S. (2019), Biabani, M., Izadpanah, S. (2019).…”
Section: Punto De Partidaunclassified